Emotional State of Chinese Healthcare Workers During COVID-19 Pandemic - Jiang, Minggang; Shao, Xu; Rao, Shengyi; Ling, Yu; Pi, Zhilian; Shao, Yongqiang; Zhao, Shuaixiang; Yang, Li; Wang, Huiming; Chen, Wei; Tang, Jinsong (Frontiers in Psychology, 2022)
Objective: Anti-epidemic work against COVID has become routine work in China. Our study was intended to investigate the emotional and psychological state of healthcare workers and look for the association between sociodemographic factors/ profession-related condition and emotional state. Method: A cross-sectional survey was conducted online among healthcare workers. Anxiety and depression were assessed by the Chinese versions of the 7-item Generalized Anxiety Disorder (GAD-7) and the 9-item Patient Health Questionnaire (PHQ-9) respectively. Workplace violence, profession, and attitude related to COVID pandemic were recorded. Wherever suitable, independent t test and one-way ANOVA were performed to detect group differences of GAD-7 and PHQ-9 total scores after grouping by sociodemographic variables, experience of workplace violence, and anti-epidemic participation respectively. Multiple linear regression analyses were utilized in order to look for the potential associated factors of GAD-7 and PHQ-9. Results: Among 2139 people, 86.44% of participants had minimal symptoms of anxiety, 11.08% mild, 1.59% moderate, and 0.89% severe. Meanwhile, 81.34% had minimal symptoms of depression, 14.07% mild, 2.90% moderate, 1.17% moderately severe, and 0.51% severe. Student t test showed that participants with female gender, with experience of workplace violence scored higher on both GAD-7 and PHQ-9, and participants with experience of anti-epidemic front-line work during pandemic scored lower on both GAD-7 and PHQ-9. ANOVA showed that participants aging from 31 to 40, with higher educational level, with middle level of annual after-tax income, with department of internal medicine or surgery, or with middle level of job title scored higher on both GAD-7 and PHQ-9. Regression analyses showed that female gender, high job title, and experience of workplace violence positively were associated with anxiety or depression. Doctoral education, nonmainstream department, job enthusiasm, and professional self-identity were negatively associated with anxiety or depression. Additionally, psychological support was negatively associated with depression. Conclusion: Our study revealed that gender, educational level, department category, job title, experience of workplace violence, job enthusiasm, and professional self-identity are the most important influencing factors of physician’s anxiety and depression. Self-tailored psychological intervention should be based on the predisposing factors above to mentally prepare healthcare workers for this long-lasting battle against COVID-19.